The Turkish long-necked lute saz or bağlama - Zeeuw, Hans de, (Archaeopress Publishing Ltd, 2020)
The saz or bağlama, a generic name for long-necked lutes in Turkey, plays an important role in Turkish musical culture. This volume focuses on the instrument's cultural-historical background while briefly discussing various saz or bağlama types and their construction, tuning, and playing techniques.